Squandering in Ethic Economics: Consumer and Producer Behaviors Analysis - Bidabad, Bijan (International Journal of Islamic Business & Management, 2019)
Purpose: This paper investigates the effects of squandering on the economic behavior of consumer and firm. Moreover, we analyze consumer work-leisure behavior from the squandering viewpoint. Findings: Commodity squandering creates no utility for the consumer. Just the "(real) consumption (usage)" satisfies the preference ordering rules of consumer behavior and the "squandered" commodities do not satisfy these rules. Definitionally, consumption is equal to "real usage" plus "squandered" commodities. Thence, the consumer will lose some parts of her utility because of squandering (because of lost resources). The amount of lost income resources due to squandering should be recompensated by more works to preserve the consumer’s welfare constant. Squandering effects in total productivity, non-optimal allocation of production factors, product wastage, and product decay are analyzed as less productivity and less supply of products due to squandering. According to this analysis, theoretically, it can be concluded that squandering will decrease the leisure and its corresponding utility of human being. Social implications: If the ethic economics’ doctrine affects the consumption pattern, this process will moderate consumption. Otherwise, the society will move toward exploiting all of her capital to: "just produce-just consume". The latter will be intensified by knowledge-based economic progress. JEL: D11, D21, Z12, D19, D24 DOI: https://doi.org/10.5281/zenodo.3402339